2007
DOI: 10.1136/bjo.2007.122283
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of intravitreal bevacizumab for polypoidal choroidal vasculopathy

Abstract: Intravitreal injection of bevacizumab may reduce the fluid from PCV but seems to be ineffective for diminishing its choroidal vascular changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
155
3
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 230 publications
(167 citation statements)
references
References 34 publications
7
155
3
2
Order By: Relevance
“…18 This difference in the response to the anti-VEGF therapy may be one reason for the low rate of polyp regression after anti-VEGF therapy for PCV. 25,26 Further investigations are needed to address the issue.…”
Section: Discussionmentioning
confidence: 99%
“…18 This difference in the response to the anti-VEGF therapy may be one reason for the low rate of polyp regression after anti-VEGF therapy for PCV. 25,26 Further investigations are needed to address the issue.…”
Section: Discussionmentioning
confidence: 99%
“…Anti-VEGF was reported to have a lower efficacy in eradicating the polypoidal choroidal structure in eyes with PCV, given the persistence of polypoidal lesions or branching vascular networks in previous reports using anti-VEGF as sole treatment. [12][13][14][15][16] However, the high anatomic conversion rate by verteporfin PDT is not without costs. PDT may cause putative damages to the PRE by causing choriocapillary hypoperfusion and retinal pigment epithelium atrophy.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Considering the molecular weight (ranibizumab is a 48-kDa Fab fragment, whereas bevacizumab is a complete 149-kDa antibody), ranibizumab may be more effective in treatment of PCV because of its smaller molecular weight and possible deeper penetration to choroidal vascular abnormality lesions of PCV. 17 In addition, ranibizumab is affinity matured and may provide better VEGF inhibition through stronger molecular binding, compared with bevacizumab.…”
Section: Intravitreal Bevacizumabmentioning
confidence: 99%
“…10 Bevacizumab (a humanized full-length anti-VEGF antibody) also appears to have a treatment effect in PCV eyes. 8,9 Kokame et al 13 reported that continuous monthly intravitreal ranibizumab injection was well tolerated in PCV patients; in addition, patients showed stabilized vision and decreased macular edema.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation